Influence of Service Quality on Students’ Satisfaction in Using the Library of UPN "Veteran" Jatim - Rusdi Hidayat; Megahnanda A.K; Herlina Suksmawati (Nusantara Science and Technology Proceedings)
Many people stated that the library is the heart of university. This study is conducted it the Library of UPN “Veteran” of East Java. Library of UPN "Veteran" of East Java provides services to the users based on the dimensions determined in servqual. Nevertheless, the application of indirect servqual dimension assurances the satisfaction in using library services, for it is crucial to figure out the application of servqual at the library of UPN "Veteran" of East Java so that the service provided by the staff can satisfy the library user.The purposes of this study are 1) to determine the effect of service quality (reliability, responsiveness, assurance, empathy and direct evidence) to the students’ satisfaction in using the library of UPN "Veteran" of East Java, 2) Service quality dimension that mostly affect students satisfaction of UPN "Veterans" of East Java. The method used in this study is a survey method using questionnaires as a tool of data collection, with the unit of analysis is a student of the library in UPN "Veteran" of East Java. The sampling technique in this research is Simple Random Sampling. The data analysis technique used in this research is Multiple Linear Regression to find out the dimension of reliability, responsiveness, assurance, empathy, and direct evidence which simultaneously or partially influence to the students’ satisfaction in using the library of UPN "Veteran" of East Java. The interim results of this study showed that the quality of service (reliability, responsiveness, assurance, empathy and direct evidence) simultaneously have a significant effect on the students’ satisfaction on the library services of UPN "Veteran" of East Java. Secondly, the dimensions of reliability, responsiveness, empathy and direct evidence have a significant effect on student satisfaction while the assurance dimension has no significant effect.